Haboobs: convectively generated dust storms in West Africa - Roberts, Alexander J.; Knippertz, Peter (Weather, 2012)
WeatherVolume 67, Issue 12 p. 311-316 Research Article Haboobs: convectively generated dust storms in West Africa† Alex Roberts, Corresponding Author Alex Roberts School of Earth and Environment, Faculty of Environment, University of LeedsCorrespondence to: Alex Roberts, [email protected]Search for more papers by this authorPeter Knippertz, Peter Knippertz School of Earth and Environment, Faculty of Environment, University of LeedsSearch for more papers by this author Alex Roberts, Corresponding Author Alex Roberts School of Earth and Environment, Faculty of Environment, University of LeedsCorrespondence to: Alex Roberts, [email protected]Search for more papers by this authorPeter Knippertz, Peter Knippertz School of Earth and Environment, Faculty of Environment, University of LeedsSearch for more papers by this author First published: 29 November 2012 https://doi.org/10.1002/wea.1968Citations: 35 † This article is based on a presentation to the RMetS Student Conference in July 2011. Read the full textAboutPDF ToolsRequest permissionExport citationAdd to favoritesTrack citation ShareShare Give accessShare full text accessShare full-text accessPlease review our Terms and Conditions of Use and check box below to share full-text version of article.I have read and accept the Wiley Online Library Terms and Conditions of UseShareable LinkUse the link below to share a full-text version of this article with your friends and colleagues. Learn more.Copy URL Share a linkShare onEmailFacebookTwitterLinkedInRedditWechat References Atlas D , Williams CR. 2003. The anatomy of a continental tropical convective storm. J. Atmos. Sci. 60: 3–15. Benjamin TB . 1968. Gravity currents and related phenomena. J. Fluid Mech. 30: 209–248. Buckle C. 2004. Weather and Climate in Africa, 2nd Edition. Longman: Harlow, UK. Byers HR . 1949. Structure and dynamics of the thunderstorm. Science 110: 291–294. Derbyshire E. 2007. Natural minerogenic dust and human health. AMBIO: A J. Hum. Environ. 36: 73–77. Engelstaedter S , Tegen I, Washington R. 2006. North African dust emissions and transport. Earth Sci. Rev. 79: 73–100. Fujita TT , Byers HR. 1977. Spearhead echo and downburst in the crash of an airliner. Mon. Weather Rev. 105: 129–146. Goudie AS . 2009. Dust storms: recent developments. J. Environ. Manage. 90: 89–94. Houze RA . 1993. Chapter 9: mesoscale convective systems, Cloud Dynamics, 338–346. Academic Press: San Diego, CA. Jickells TD , An ZS, Andersen KK, et al. 2005. Global iron connections between desert dust, ocean biogeochemistry and climate. Science 308: 67–71. Johnson RH , Mapes BE. 2001. Mesoscale processes and severe convective weather, in Severe Convective Storms, 76–78. CA Doswell (ed.). American Meteorological Society: Boston, MA. Laing AG , Carbone RE, Levizzani V. 2011. Cycles and propagation of deep convection over equatorial Africa. Mon. Weather Rev. 139: 2832–2853. Laing AG , Fritsch JM. 2000. The large-scale environments of the global populations of mesoscale convective complexes. Mon. Weather Rev. 128: 2756–2776. Liu C , Moncrieff MW. 1996. A numerical study of the effects of ambient flow and shear on density currents. Mon. Weather Rev. 124: 2282–2303. Marsham JH , Knippertz P, Dixon N, Parker DJ, Lister GMS. 2011. The importance of the representation of deep convection for modeled dust dust-generating winds over West Africa during summer. Geophys. Res. Lett. 38: L16803. Marsham JH , Parker DJ, Grams CM, Taylor CM, Haywood JM. 2008. Uplift of Saharan dust south of the intertropical discontinuity. J. Geophys. Res. 113: D21102. Ross AN , Tompkins AM, Parker DJ. 2004. Simple models of the role of surface fluxes in convective cold pool evolution. J. Atmos. Sci. 61: 1582–1595. Rotunno R , Klemp JB, Weisman ML. 1988. A theory for strong, long-lived squall lines. J. Atmos. Sci. 45: 463–485. Shao Y , Wyrwoll KH, Chappell A, et al. 2011. Dust cycle: an emerging core theme in Earth system science. Aeolian Res. 2: 181–204. Simpson JE . 1997. Gravity Currents in the Environment and the Laboratory, 2nd Edition. Cambridge University Press: Cambridge, UK. Sterk G. 2003. Cause, consequence and control of wind erosion in Sahelian Africa: a review. Land Degrad. Dev. 14: 95–108. Sultan B , Labadi K, Guégan JF, Janicot S. 2005. Climate drives the meningitis epidemics onset in West Africa. PLoS Med. 2: e6. Citing Literature Volume67, Issue12December 2012Pages 311-316 ReferencesRelatedInformation
openalex: W2073148724 mag: 2073148724
Keywords: openalex:import

Increasing manmade air pollution reduces rainfall in southern West Africa - Pante, Gregor; Knippertz, Peter; Fink, Andreas H.; Kniffka, Anke (EGUGA, 2019)
openalex: W3041010172 mag: 3041010172
Keywords: openalex:import

The possible role of local air pollution in climate change in West Africa - Knippertz, Peter; Evans, M. J.; Field, Paul R.; Fink, Andreas H.; Liousse, Catherine; Marsham, John H. (Nature Climate Change, 2015)
Here it is argued that air pollution over West African cities needs greater consideration. The effects of aerosol pollution on clouds and solar and thermal radiation can be expected to alter regional climate and impact human health and food security. The climate of West Africa is characterized by a sensitive monsoon system that is associated with marked natural precipitation variability. This region has been and is projected to be subject to substantial global and regional-scale changes including greenhouse-gas-induced warming and sea-level rise, land-use and land-cover change, and substantial biomass burning. We argue that more attention should be paid to rapidly increasing air pollution over the explosively growing cities of West Africa, as experiences from other regions suggest that this can alter regional climate through the influences of aerosols on clouds and radiation, and will also affect human health and food security. We need better observations and models to quantify the magnitude and characteristics of these impacts.
openalex: W1851047940 mag: 1851047940
Keywords: openalex:import

The possible role of local air pollution in climate change in West Africa - Knippertz, Peter; Evans, M. J.; Field, Paul R.; Fink, Andreas H.; Liousse, Catherine; Marsham, John H. (Nature Climate Change, 2015)
Here it is argued that air pollution over West African cities needs greater consideration. The effects of aerosol pollution on clouds and solar and thermal radiation can be expected to alter regional climate and impact human health and food security. The climate of West Africa is characterized by a sensitive monsoon system that is associated with marked natural precipitation variability. This region has been and is projected to be subject to substantial global and regional-scale changes including greenhouse-gas-induced warming and sea-level rise, land-use and land-cover change, and substantial biomass burning. We argue that more attention should be paid to rapidly increasing air pollution over the explosively growing cities of West Africa, as experiences from other regions suggest that this can alter regional climate through the influences of aerosols on clouds and radiation, and will also affect human health and food security. We need better observations and models to quantify the magnitude and characteristics of these impacts.
openalex: W1851047940 mag: 1851047940
Keywords: openalex:import

The possible role of local air pollution in climate change in West Africa - Knippertz, Peter; Evans, M. J.; Field, Paul R.; Fink, Andreas H.; Liousse, Catherine; Marsham, John H. (Nature Climate Change, 2015)
Here it is argued that air pollution over West African cities needs greater consideration. The effects of aerosol pollution on clouds and solar and thermal radiation can be expected to alter regional climate and impact human health and food security. The climate of West Africa is characterized by a sensitive monsoon system that is associated with marked natural precipitation variability. This region has been and is projected to be subject to substantial global and regional-scale changes including greenhouse-gas-induced warming and sea-level rise, land-use and land-cover change, and substantial biomass burning. We argue that more attention should be paid to rapidly increasing air pollution over the explosively growing cities of West Africa, as experiences from other regions suggest that this can alter regional climate through the influences of aerosols on clouds and radiation, and will also affect human health and food security. We need better observations and models to quantify the magnitude and characteristics of these impacts.
openalex: W1851047940 mag: 1851047940
Keywords: openalex:import

The possible role of local air pollution in climate change in West Africa - Knippertz, Peter; Evans, M. J.; Field, Paul R.; Fink, Andreas H.; Liousse, Catherine; Marsham, John H. (Nature Climate Change, 2015)
Here it is argued that air pollution over West African cities needs greater consideration. The effects of aerosol pollution on clouds and solar and thermal radiation can be expected to alter regional climate and impact human health and food security. The climate of West Africa is characterized by a sensitive monsoon system that is associated with marked natural precipitation variability. This region has been and is projected to be subject to substantial global and regional-scale changes including greenhouse-gas-induced warming and sea-level rise, land-use and land-cover change, and substantial biomass burning. We argue that more attention should be paid to rapidly increasing air pollution over the explosively growing cities of West Africa, as experiences from other regions suggest that this can alter regional climate through the influences of aerosols on clouds and radiation, and will also affect human health and food security. We need better observations and models to quantify the magnitude and characteristics of these impacts.
openalex: W1851047940 mag: 1851047940
Keywords: openalex:import

The Ewiem Nimdie Summer School Series in Ghana: Capacity Building in Meteorological Education and Research—Lessons Learned and Future Prospects - Tompkins, Adrian M.; Parker, Douglas J.; Danour, Sylvester; Amekudzi, Leonard K.; Bain, Caroline L.; Dominguez, Abdul; Douglas, Michael W.; Fink, Andreas H.; Grimes, D. I. F.; Hobby, Matthew; Knippertz, Peter; Lamb, Peter; et al. (Bulletin of the American Meteorological Society, 2012)
Nimdie summer school is a biennial or triennial event that to date has been hosted in Ghana and focuses on the atmospheric sciences; "Ewiem Nimdie" means "atmospheric science" in the local Ashanti language.The first school was conducted in the summer of 2008, hosted by the Kwame Nkrumah University of Science and Technology (KNUST) located in Kumasi, with the second school taking place at the same institution two years later, in July 2010.The schools were designed to help launch the undergraduate meteorology program of KNUST and benefited from the significant increase in research activity regarding West African weather and climate that has arisen from the African Monsoon Multidisciplinary Analysis (AMMA) program.Both schools lasted two weeks and included a broad program of lectures, hands-on classes in regional forecasting and climate applications modeling, and a variety of field measurement activities with associated student projects that were presented at the culmination of each school.From its inception, the summer school program was designed around the concept of integrating undergraduate and new Ph.D. students from all over the globe with research interests in African meteorology and climate.Figure 1 documents the country of study/origin of the students who participated in each school.The attendance of African students from across the continent was funded under the budget of each school, with about half originatingThe ewiem Nimdie Summer School SerieS
openalex: W2016235198 mag: 2016235198
Keywords: openalex:import

The Ewiem Nimdie Summer School Series in Ghana: Capacity Building in Meteorological Education and Research, Lessons Learned, and Future Prospects - Tompkins, Adrian M.; Parker, Douglas J.; Danour, Sylvester; Amekudzi, Leonard K.; Bain, Caroline L.; Dominguez, Abdul; Douglas, Michael W.; Fink, Andreas H.; Grimes, D. I. F.; Hobby, Matthew; Knippertz, Peter; Lamb, J.; et al. (Bulletin of the American Meteorological Society, 2012)
"The Ewiem Nimdie Summer School Series in Ghana: Capacity Building in Meteorological Education and Research, Lessons Learned, and Future Prospects" published on May 2012 by American Meteorological Society.
openalex: W4253502736
Keywords: openalex:import

Remote biomass burning dominates southern West African air pollution during the monsoon - Haslett, Sophie L.; Taylor, Jonathan; Evans, M. J.; Morris, Eleanor; Vogel, Bernhard; Dajuma, Alima; Brito, Joël; Batenburg, A. M.; Borrmann, Stephan; Schneider, Johannes; Schulz, Christiane; Denjean, Cyrielle; et al. (Atmospheric chemistry and physics (Print), 2019)
Abstract. Vast stretches of agricultural land in southern and central Africa are burnt between June and September each year, which releases large quantities of aerosol into the atmosphere. The resulting smoke plumes are carried west over the Atlantic Ocean at altitudes between 2 and 4 km. As only limited observational data in West Africa have existed until now, whether this pollution has an impact at lower altitudes has remained unclear. The Dynamics-aerosol-chemistry-cloud interactions in West Africa (DACCIWA) aircraft campaign took place in southern West Africa during June and July 2016, with the aim of observing gas and aerosol properties in the region in order to assess anthropogenic and other influences on the atmosphere. Results presented here show that a significant mass of aged accumulation mode aerosol was present in the southern West African monsoon layer, over both the ocean and the continent. A median dry aerosol concentration of 6.2 µg m−3 (standard temperature and pressure, STP) was observed over the Atlantic Ocean upwind of the major cities, with an interquartile range from 5.3 to 8.0 µg m−3. This concentration increased to a median of 11.1 µg m−3 (8.6 to 15.7 µg m−3) in the immediate outflow from cities. In the continental air mass away from the cities, the median aerosol loading was 7.5 µg m−3 (5.9 to 10.5 µg m−3). The accumulation mode aerosol population over land displayed similar chemical properties to the upstream population, which implies that upstream aerosol is a significant source of aerosol pollution over the continent. The upstream aerosol is found to have most likely originated from central and southern African biomass burning. This demonstrates that biomass burning plumes are being advected northwards, after being entrained into the monsoon layer over the eastern tropical Atlantic Ocean. It is shown observationally for the first time that they contribute up to 80 % to the regional aerosol loading in the monsoon layer over southern West Africa. Results from the COSMO-ART (Consortium for Small-scale Modeling – Aerosol and Reactive Trace gases) and GEOS-Chem models support this conclusion, showing that observed aerosol concentrations over the northern Atlantic Ocean can only be reproduced when the contribution of transported biomass burning aerosol is taken into account. As a result, the large and growing emissions from the coastal cities are overlaid on an already substantial aerosol background. Simulations using COSMO-ART show that cloud droplet number concentrations can increase by up to 27 % as a result of transported biomass burning aerosol. On a regional scale this renders cloud properties and precipitation less sensitive to future increases in anthropogenic emissions. In addition, such high background loadings will lead to greater pollution exposure for the large and growing population in southern West Africa. These results emphasise the importance of including aerosol from across country borders in the development of air pollution policies and interventions in regions such as West Africa.
openalex: W2938925735 mag: 2938925735
Keywords: openalex:import

Remote biomass burning dominates southern West African air pollution during the monsoon - Haslett, Sophie L.; Taylor, Jonathan; Evans, M. J.; Morris, Eleanor; Vogel, Bernhard; Dajuma, Alima; Brito, Joël; Batenburg, A. M.; Borrmann, Stephan; Schneider, Johannes; Schulz, Christiane; Denjean, Cyrielle; et al. (2019)
Abstract. Vast quantities of agricultural land in southern and central Africa are burnt between June and September each year, which releases large concentrations of aerosols into the atmosphere. The resulting smoke plumes are carried west over the Atlantic Ocean at altitudes between 2 and 4 km. As only limited observational data in West Africa have existed until now, whether this pollution has an impact at lower altitudes has remained unclear. The Dynamics-Aerosol-Chemistry-Cloud Interactions in West Africa (DACCIWA) aircraft campaign took place in southern West Africa during June and July 2016, with the aim of observing gas and aerosol properties in the region in order to assess anthropogenic and other influences on the atmosphere. Results presented here show that a significant mass of aged accumulation mode aerosol was present in the southern West African boundary layer, over both the ocean and the continent. A median dry aerosol concentration of 6.2 µg m−3 (standard temperature and pressure (STP)) was observed over the Atlantic Ocean upwind of the major cities, with an interquartile range from 5.3 to 8.0 µg m−3. This concentration increased to a median of 11.1 µg m−3 (8.6 to 15.7 µg m−3) in the immediate outflow from cities. In the continental air mass away from the cities, the median aerosol loading was 7.5 µg m−3, with an interquartile range of 4.2 µg m−3. The accumulation mode aerosol population over land displayed similar chemical properties to the upstream population, which implies that upstream aerosol is a significant source of aerosol pollution over the continent. The upstream aerosol is found to have most likely originated from central and southern African biomass burning. This demonstrates that biomass burning plumes are being advected northwards, after being entrained into the monsoon layer over the eastern tropical Atlantic Ocean. It is shown observationally for the first time that they contribute up to 80 % to the regional aerosol loading in the boundary layer of southern West Africa during the monsoon season. As a result, the large and growing emissions from the coastal cities are overlaid on an already substantial aerosol background. On a regional scale this renders cloud properties and precipitation less sensitive to future increases in anthropogenic emissions. Such high background loadings will lead to greater pollution exposure for the large and growing population in southern West Africa. These results emphasise the importance of including aerosol from across country borders in the development of air pollution policies and interventions in regions such as West Africa.
openalex: W4240559130
Keywords: openalex:import